Barriers and enablers to young people accessing sexual and reproductive health services in Pacific Island Countries and Territories: A scoping review. - Maggie Ikinue Baigry; Robin Ray; Daniel Lindsay; Angela Kelly-Hanku; Michelle Redman-MacLaren (PLoS ONE)
Background The number of young people utilising sexual and reproductive health services in Pacific Island Countries and Territories remains poor despite the availability and the existence of the fundamental rights to access these services. Adolescents and youth need accurate information and timely access to contraceptives to prevent adverse consequences associated with unintended pregnancies, abortion, childbirth and untreated sexually transmitted infections. This scoping review identifies and analyses factors contributing to young people's low access to sexual and reproductive health information and services in this region. Methods Guided by the PRISMA Scoping review guidelines, we searched three databases (Medline Ovid, Scopus and CINAHL Complete) for peer-reviewed articles published between 1st January 2000 and 31st August 2020 that reported on factors, including barriers and enablers, affecting access to sexual and reproductive health information and services by young people living in Pacific Island Countries and Territories. We assessed the quality of each study according to the study designs, methods of data collection, data analysis and ethical considerations. All information was sorted and organised using an Excel Spreadsheet. Text data from published articles were charted inductively using thematic analysis with no predetermined codes and themes. Findings Five hundred eighty-nine articles were screened, and only eight met the inclusion criteria outlined in this scoping review protocol. These eight articles reported studies conducted in four Pacific Island Countries and Territories: Cook Islands, Fiji, Papua New Guinea, and Vanuatu. Factors such as lack of accurate sexual and reproductive health knowledge and social stigma were the leading causes of young people's limited access to sexual and reproductive health services. Cultural and religious beliefs also invoked stigmatising behaviours in some family and community members. Conclusion This scoping review revealed that social stigma and judgemental attitudes imposed by family and community members, including healthcare providers, hinder young unmarried individuals in Pacific Island Countries and Territories from accessing sexual and reproductive health information and contraceptives. Alternatively, a non-judgmental healthcare provider is perceived as an enabler in accessing sexual and reproductive health information and services. Moreover, given that only a few studies have actually focused on young people's sexual and reproductive health needs in the region, more research is required to fully understand the health-seeking behaviours of young people in their specific contexts.